Evaluation of microvascular findings of deeply invasive colorectal cancer by endocytoscopy with narrow-band imaging - Nakamura, Hiroki; Kudo, Shin-ei; Misawa, Masashi; Kataoka, Shinichi; Wakamura, Kunihiko; Hayashi, Takemasa; Kudo, Toyoki; Mori, Yuichi; Takeda, Kenichi; Ichimasa, Katsuro; Miyachi, Hideyuki; Katagiri, Atushi; Ishida, Fumio; Inoue, Haruhiro (Endoscopy International Open, 2016)
Background and study aims: Magnifying narrow-band imaging (NBI) is useful for examination of colorectal lesions, and endocytoscopy (EC) allows diagnostic evaluation of structural atypia, nuclear atypia, and vascular structures of colorectal tumors. The aim of this study was to examine surface microvessels in deep invasive colorectal cancer using EC with a new NBI video processor system.Patients and methods: We retrospectively assessed 132 colorectal neoplastic lesions: 81 adenomas, 18 intramucosal cancers, 4 submucosal slightly invasive cancers, and 29 submucosal deep invasive cancers. Detailed vascular findings commonly seen in submucosal deep invasive carcinomas included > 2-fold vasodilatation seen in adenomas, abnormal tortuosity and branching, loss of the micro-network pattern, caliber change in > 2 places in a single blood vessel, and blood vessels not visible in a line because they appear like a string of beads (beaded sign).Results: Univariate analysis revealed 4 vascular findings that were strongly predictive of submucosal deep invasion: vasodilatation (odds ratio [OR] 9.31; 95 % confidence interval [CI] 3.57 – 24.30), loss of the micro-network pattern (OR 61.60; 95 % CI 17.87 – 212.29), caliber change (OR 35.7; 95 % CI 9.16 – 139.14), and the beaded sign (OR 45.90; 95 % CI 5.50 – 382.73).Conclusions: Detailed assessment of ultra-magnified microvessels could improve the diagnostic performance for submucosal deep invasive cancer. Study registration: UMIN-CTR000014033